Paraneoplastic hyperthyroidism. (15th August 2011) - Kohler, Sibylle; Tschopp, Oliver; Jacky, Emanuel; Schmid, Christoph
Abstract : The authors describe a 31-year-old male with a metastatic germ cell tumour and massively elevated human chorionic gonadotrophin (HCG) levels who presented with hyperthyroidism. As HCG is structurally closely related to thyroid stimulating hormone (TSH), it can activate the TSH receptor; grossly elevated levels may result in hyperthyroidism. After initiation of chemotherapy, HCG levels decreased and hyperthyroidism resolved.